Differential accumulation of gliadin proteins in wheat grain of RILs grown at two different agroclimatic conditions and their effect on loaf volume - Elangovan, M.; Dholakia, Bhushan B.; Gaikwad, S. M.; Gupta, V. S. (Australian Journal of Crop Science, 2010)
The end use of wheat depends on the quality and quantity of protein accumulated in the grain during the grain filling stage. Gliadin families of proteins are proved to affect the bread making quality (BMQ) by affecting the rheology and functionality of dough. The gliadin accumulation was analysed using Indian genotypes grown in two diverse agro climatic zones. About 16 RILs along with their parents HI977 and HD2329 revealed significant difference in accumulation of all gliadin fractions. High accumulation of alpha and beta gliadin with low level of gamma gliadin was observed for Kota as compared to Pune location. However, this significant difference in gliadin accumulation due to environment, did not affect the loaf volume performance of the RILs at statistically significant level.
Keywords: loaf volume (Lv); RP-HPLC; Wheat protein

Data of in vitro synthesized dsRNAs on growth and development of helicoverpa armigera - Chikate, Y. R.; Dawkar, V. V.; Barbole, R. S.; Tilak, P. V.; Gupta, V. S.; Giri, A. P. (Data in Brief, 2016)
The data presented in this article is related to the research article "RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera" (Chikate et al., 2016) [1]. RNA interference (RNAi) is emerging as a potent insect pest control strategy over current methods and their resistance by pest. In this study we tested 15 different in vitro synthesized dsRNAs for gene silencing in Helicoverpa armigera. These dsRNAs were specific against H. armigera enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine proteases such as cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b). These dsRNAs were fed to second instar larvae at an optimized dose (60 μg/day) for 3 days separately. Effects of dsRNA feeding were observed in terms of larval mass gain, percentage mortality and phenotypic abnormalities in later developmental stages of H. armigera. These findings might provide potential new candidates for designing sequence-specific dsRNA as pesticide in crop protection.

Data on changes in the fatty acid composition during fruit development and ripening of three mango cultivars (Alphonso, Pairi and Kent) varying in lactone content - Deshpande, A. B.; Chidley, H. G.; Oak, P. S.; Pujari, K. H.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2016)
Data in this article presents fatty acid composition of three mango cultivars; Alphonso, Pairi and Kent through fruit development and ripening. Change in the ω-6 and ω-3 fatty acids level during mango fruit development and ripening is depicted. Also, data on aroma volatile ‘lactones’ composition from pulp and skin tissues of these cultivars at their ripe stage, respectively is provided. Statistical data is also shown, which correlates modulation in lactone content with that of fatty acid composition and content during fruit development and ripening in all the three mango cultivars.

Data on metabolic profiling of spongy tissue disorder in Mangifera indica cv. Alphonso - Oak, P. S.; Deshpande, A. B.; Pujari, K. H.; Prabhudesai, S. S.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2019)
Data in this article presents aroma volatiles and fatty acids composition of mesocarp specific malady namely spongy tissue disorder in Mangifera indica cv. Alphonso. Quantitative changes in various aroma volatile compound classes as well as saturated and unsaturated fatty acids in spongy tissue vis-à-vis healthy mesocarp have been analyzed throughout the development of the disorder. Statistical data analysis correlates the dynamic changes in the aroma volatiles composition to that of the modulation in the fatty acids profile.